2003
DOI: 10.1002/pd.715
|View full text |Cite
|
Sign up to set email alerts
|

Fetal karyotyping after 28 weeks of gestation for late ultrasound findings in a low risk population

Abstract: In low risk patients, fetal karyotyping in the third trimester may be justified when the diagnosis of fetal malformation is made in the third trimester of pregnancy. Two or more anomalies increase the risk of fetal aneuploidy even with a negative-screening test in the first and second trimester of pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 20 publications
1
30
0
Order By: Relevance
“…Hill et al described only cases with polyhydramnios that subsequently resolved prior to delivery (Hill et al, 1995), and Zahn et al focused on polyhydramnios to a degree for which hospitalization was recommended (Zahn et al, 1993). Nine studies did not specify the method they used for chromosomal sampling methods (Abele et al, 2012;Dashe et al, 2002;Biggio et al, 1999;Yaman et al, 1996;Barnhard et al, 1995;Hill et al, 1995;Glantz et al, 1994;Dombrowski et al, 1993;Hendricks et al, 1991), seven studies reported using amniocentesis (Shimada et al, 2009;Claussen et al, 1994;Zahn et al, 1993;Brady et al, 1992;Gagnon et al, 1992;Hentemann et al, 1989;Landy et al, 1987), two papers also employed cordocentesis (Drummond et al, 2003;Lee et al, 1996), and two also examined placental biopsy samples (Carlson et al, 1990;Eydoux et al, 1989) (Table S2). Of note, all the included papers performed microscopic karyotype evaluation, and no studies were found using more advanced genetic methods such as chromosomal microarray analysis (CMA).…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…Hill et al described only cases with polyhydramnios that subsequently resolved prior to delivery (Hill et al, 1995), and Zahn et al focused on polyhydramnios to a degree for which hospitalization was recommended (Zahn et al, 1993). Nine studies did not specify the method they used for chromosomal sampling methods (Abele et al, 2012;Dashe et al, 2002;Biggio et al, 1999;Yaman et al, 1996;Barnhard et al, 1995;Hill et al, 1995;Glantz et al, 1994;Dombrowski et al, 1993;Hendricks et al, 1991), seven studies reported using amniocentesis (Shimada et al, 2009;Claussen et al, 1994;Zahn et al, 1993;Brady et al, 1992;Gagnon et al, 1992;Hentemann et al, 1989;Landy et al, 1987), two papers also employed cordocentesis (Drummond et al, 2003;Lee et al, 1996), and two also examined placental biopsy samples (Carlson et al, 1990;Eydoux et al, 1989) (Table S2). Of note, all the included papers performed microscopic karyotype evaluation, and no studies were found using more advanced genetic methods such as chromosomal microarray analysis (CMA).…”
Section: Resultsmentioning
confidence: 96%
“…Eight investigations focused on pregnancies undergoing invasive cytogenetic testing, a certain proportion of which were referred due to polyhydramnios. Two of these studies included all the referred samples (Shimada et al, 2009;Claussen et al, 1994), some required the presence of second trimester ultrasound (Yaman et al, 1996;Dombrowski et al, 1993), or focused only on pregnancies above 28 weeks (Drummond et al, 2003), two included only amniocenteses performed due to sonographic abnormality (Gagnon et al, 1992;Eydoux et al, 1989), and Lee et al analyzed only cases of idiopathic polyhydramnios (Lee et al, 1996). The remaining papers focused on patients diagnosed with polyhydramnios (a certain proportion of which underwent cytogenetic testing), besides Hentemann et al (Hentemann et al, 1989), who analyzed pregnancies with any ultrasonographic abnormality (including polyhydramnios).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…With the development of obstetric ultrasound examinations for a perinatal care, fetal anomalies are often found without the objective of diagnosis (Drummond et al 2003;Yang et al 2005). Most such findings do not suggest a specific chromosome region as a target for prenatal diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Little is known about whether microarray CGH with cffDNA is a rapid and effective analytical method for diagnosis of unbalanced chromosomal aberrations, or how to use the method in uncultured amniotic fluid. In clinical medicine, situations often arise which involve pregnancies requiring a rapid prenatal diagnosis for appropriate fetal management, for example those with fetal multiple anomalies detected by ultrasound examination at late gestation (Drummond et al 2003;Nyberg and Souter 2000;Yang et al 2005). In this situation, utilization of cffDNA from crude amniotic fluid may make it possible to shorten the testing time for molecular karyotyping.…”
Section: Introductionmentioning
confidence: 99%